Potensi dan Upaya Pemanfaatan Air Tanah untuk Irigasi Lahan Kering di Nusa Tenggara - Heni Rengganis Soedireja (Balai Teknik Irigasi, 2016)
Nusa Tenggara region has a vast dry land area but they are very potential to be developed. The water availability as one of the determinants has a role in helping to increase productivity in an effort for dry land utilization. Groundwater potential can be technically applied for dry lands irrigation in Nusa Tenggara. This paper provided the study results of both potential and groundwater utilization as irrigation water resources in dry land in Nusa Tenggara, by considering groundwater potential resource, land conditions, plants variety, and water supply technology. The method used is descriptive analysis by collecting primary and secondary data through visits to several related agencies, literature studies, and field surveys. These results provide further proposed groundwater development through the conjuctive use of surface water and groundwater. Moreover, the results are expected to be used either in the proposed water resources management policy in the area or as feedback to stakeholders in groundwater utilization, particularly in the dry land as well as for further research.